9 Important Communication Skills for Every Relationship - Victor William Harris (EDIS)
Effective communication is critical to successful relationships. Researchers and therapists have found at least nine skills that can help couples learn to talk effectively about important issues, like time spent together/apart, money, health, gender differences, children, family, friends, commitment, trust, and intimacy. If learned well, these nine skills can help put our relationships on a positive trajectory for success. This 4-page fact sheet was written by Victor William Harris and published by the UF Department of Family, Youth and Community Sciences, January 2012.